Origin of ultralow phonon transport and strong anharmonicity in lead-free halide perovskites. (November 2022) - Pandey, T.; Du, Mao-Hua; Parker, David S.; Lindsay, L.
Abstract: All-inorganic lead-free halide double perovskites offer a promising avenue toward non-toxic, stable optoelectronic materials, properties that are missing in their prominent lead-containing counterparts. Their large thermopowers and high carrier mobilities also make them promising for thermoelectric applications. Here, we present a first-principles study of the lattice vibrations and thermal transport behaviors of Cs2 SnI6 and γ -CsSnI3, two prototypical compounds in this materials class. We show that conventional static zero temperature density functional theory (DFT) calculations severely underestimate the lattice thermal conductivities ( κ l ) of these compounds, indicating the importance of dynamical effects. By calculating anharmonic renormalized phonon dispersions, we show that some optic phonons significantly harden with increasing temperature (T), which reduces the scattering of heat carrying phonons and enhances calculated κ l values when compared with standard zero temperature DFT. Furthermore, we demonstrate that coherence contributions to κ l, arising from wave like phonon tunneling, are important in both compounds. Overall, calculated κl with temperature-dependent interatomic force constants, built from particle and coherence contributions, are in good agreement with available measured data, for both magnitude and temperature dependence. Large anharmonicity combined with low phonon group velocities yield ultralow κ l values, with room temperature values of 0.26 W/m-K and 0.72 W/m-K predicted for Cs2 SnI6 and γ-CsSnI3, respectively. We further show that the lattice dynamics of these compounds are highly anharmonic, largely mediated by rotation of the SnI6 octahedra and localized modes originating from Cs rattling motion. These thermal characteristics combined with their previously computed excellent electronic properties make these perovskites promising candidates for optoelectronic and room temperature thermoelectric applications. Graphical abstract: Image 1 Highlights: Our work reveals fundamental mechanisms behind the ultralow lattice thermal conductivity of halide perovskites − Cs2 SnI6 and γ-CsSnI3 . Coherence contributions from wave like tunneling of phonons are important and contribute ∼25% to total thermal conductivity at 300K. We show that including temperature dependence for the interatomic force constants is necessary to capture the strong anharmonicity. High anharmonicity in these compounds is largely mediated by rotation of the SnI6 octahedra and localized modes originating from Cs rattling motion.